Association between lipid accumulation product and chronic obstructive pulmonary disease: a cross-sectional study based on U.S. adults - Hua, Xingshi; Liu, Ying; Xiao, Xiaoyu (Frontiers in Nutrition, 2025)
BackgroundLipid Accumulation Product (LAP), which is derived from measurements of waist circumference and triglyceride (TG) levels, serves as a comprehensive indicator of lipid accumulation. Emerging research indicates that lipid accumulation dysfunction might significantly contribute to the pathogenesis of Chronic Obstructive Pulmonary Disease (COPD). Nevertheless, the investigation into the association between LAP and COPD risk is still insufficient, particularly in population-based research. This research intends to examine the possible correlation between LAP and the likelihood of developing COPD.MethodsThis study, designed as a cross-sectional analysis, made use of data gathered from the National Health and Nutrition Examination Survey (NHANES) spanning the years 2017 to 2020, encompassing a total of 7,113 eligible participants. LAP, the exposure variable, was calculated using waist circumference and triglyceride concentration. COPD diagnosis was determined using participants’ self-reported information. To explore the association between LAP and COPD, multivariate logistic regression models were applied, and smoothing curve fitting was employed to examine any potential nonlinear patterns. Further analysis included stratified subgroup evaluations to assess how variables such as sex, smoking habits, and alcohol intake might impact the relationship between LAP and COPD.ResultsThe findings indicated a significant increase in COPD risk with each one-unit rise in ln LAP, as evidenced by an Odds Ratio (OR) of 1.16 [95% Confidence Interval (CI): 1.04–1.30, p < 0.01]. Furthermore, a quartile-based analysis revealed that individuals in the highest ln LAP category had a considerably higher likelihood of developing COPD compared to those in the lowest category, with an OR of 1.35 (95% CI: 1.04–1.75, P for trend <0.01). Furthermore, the smoothing curve fitting identified a nonlinear and positive association between ln LAP and COPD, suggesting a steeper increase in risk as ln LAP values rise. Subgroup analysis suggested that this association remained fairly consistent across various demographic groups.ConclusionThis study found a significant link between higher LAP levels and an elevated risk of COPD, with the association displaying a nonlinear pattern. As a marker of lipid accumulation abnormalities, LAP may serve as a valuable tool for assessing COPD risk and could inform strategies for early identification and targeted clinical management.